Examining The Principle of Openness in The Implementation of The Law-Making Process in Indonesia (Legal Study of Perppu Number 2 of 2022) - Lady Tri Sonic (Universitas Muhammadiyah Surakarta, 2024)
The Job Creation Law ultimately gave rise to a statement that it did not fulfill the principle of openness in the law formation process. The replacement regulation, namely